The Influence of Basic Mathematical Ability on Science Performance among Pre-service Madrasah Ibtidaiyah Teachers - Anita Ekantini; Efi Tri Astuti; Faisal Ashar Naim; Ruqoyyah Amilia Andania (Al Ibtida: Jurnal Pendidikan Guru MI, 2026)
Background: Many pre-service Madrasah Ibtidaiyah teachers experience difficulties in solving physics-related science problems despite understanding the underlying scientific concepts. These difficulties are frequently associated with inadequate mastery of basic mathematical skills. Although previous studies have reported a relationship between mathematics and physics learning, empirical evidence examining basic mathematical ability as a predictor of science performance among pre-service elementary Islamic teachers remains limited. Aims: This study aimed to examine the influence of basic mathematical ability on the science performance of pre-service Madrasah Ibtidaiyah teachers enrolled in the Advanced Science course and to determine the extent to which basic mathematical ability predicts students' science performance. Methods: A quantitative correlational design was employed involving 63 fourth-semester of pre-service Madrasah Ibtidaiyah teachers selected through total sampling. Data were collected using a basic mathematics test covering number operations, fractions, decimals, and exponents, and a science performance test covering temperature and heat, Newton's laws, work and energy, impulse and momentum, quantities and units, and the solar system. After satisfying the assumptions of normality and linearity, the data were analyzed using simple linear regression. Results: The findings revealed that basic mathematical ability significantly predicted science performance (p < .001). The regression analysis yielded a coefficient of determination (R²) of 0.578, indicating that basic mathematical ability explained 57.8% of the variance in students' science performance. The positive regression coefficient further demonstrated that higher levels of basic mathematical ability were associated with better science performance. Conclusions: Basic mathematical ability serves as a foundational cognitive prerequisite and a strong predictor of science performance among pre-service Madrasah Ibtidaiyah teachers. These findings extend the evidence on the central role of mathematical competence in science learning by demonstrating its substantial predictive contribution within the context of Islamic elementary teacher education.